Local pragmatics in a Gricean framework. Issue 5 (4th July 2017) - Simons, Mandy
Abstract: The pragmatic framework developed by H.P. Grice in "Logic and Conversation" explains how a speaker can mean something more than, or different from, the conventional meaning of the sentence she utters. But it has been argued that the framework cannot give a similar explanation for cases where these pragmatic effects impact the understood content of an embedded clause, such as the antecedent of a conditional, a clausal disjunct, or the clausal complement of a verb. In this paper, I show that such an explanation is available. One of the central arguments of the paper (Section 2) is that in a significant subset of cases, local pragmatic effects are a consequence of a global (utterance-level) pragmatic requirement. In these cases, local pragmatic effects are a consequence of 'acting locally' to resolve a potential global pragmatic violation. These cases do not require us to posit application of pragmatic principles (Maxims of Conversation) to the contents of embedded clauses. The account does, though, require the assumption that interpreters can identify and reason about the contents of unasserted sub-parts of sentences, an assumption that I motivate in section 3. Building on this, in section 4 of the paper, I argue that once we have recognized that interpreters can, and do, reason independently about the contents of non-asserted clauses, it becomes unproblematic to assume that in some cases, Gricean conversational principles do apply directly to these contents, providing an alternative route to account for local pragmatic effects. In revisiting the ideas of this paper in my response to the commentaries, I consider in more detail the revisions to Grice's broader program that are necessitated by these moves, in particular acknowledging the problematicity of Grice's notion of what is said . I argue that the starting point for Gricean reconstructions should instead be merely what is expressed, which carries no pragmatic commitments regarding what is speaker meant.